Nutritional control of cell size by the Greatwall-endosulfine-PP2A·B55 pathway - Chica, N; Rozalén, A; Pérez-Hidalgo, L; Rubio, A; Novak, B; Moreno, S (Elsevier, 2016)
Proliferating cells adjust their cell size depending on the nutritional environment. Cells are large in rich media and small in poor media. This physiological response has been demonstrated in both unicellular and multicellular organisms. Here we show that the greatwall-endosulfine (Ppk18-Igo1 in fission yeast) pathway couples the nutritional environment to the cell-cycle machinery by regulating the activity of PP2A·B55. In the presence of nutrients, greatwall (Ppk18) protein kinase is inhibited by TORC1 and PP2A·B55 is active. High levels of PP2A·B55 prevent the activation of mitotic Cdk1·Cyclin B, and cells increase in size in G2 before they undergo mitosis. When nutrients are limiting, TORC1 activity falls off, and the activation of greatwall (Ppk18) leads to the phosphorylation of endosulfine (Igo1) and inhibition of PP2A·B55, which in turn allows full activation of Cdk1·CyclinB and entry into mitosis with a smaller cell size. Given the conservation of this pathway, it is reasonable to assume that this mechanism operates in higher eukaryotes, as well.